Investigation of removal MgO Content from Flotation Concentrate of the Nickel - Copper Ores in Jinchuan - Lu S; Zhou S (The Australasian Institute of Mining and Metallurgy, 1996)
The flash smelting technology employed in Jinchuan demands a better mineral processing concentrate with an MgO content below 6.5 per cent. Two ways for MgO removal have been investigated in detail based on properties and process mineralogical characteristics of the rich ores in the number one mining area in Jinchuan. The key to the first way is the use of a new flowsheet which has two-stage grinding and separation followed by single-stage regrinding and multi-stage cleaning for the rougher concentrate. The second approach utilises two novel reagents, AT-131 and AT-202, which have been developed recently. Excellent metallurgical performance has been obtained in a commercial test and a batch test, respectively. The MgO content of flotation concentrate can be reduced to about six per cent.